STRATEGI PENGEMBANGAN USAHA MADU HUTAN BERBASIS KELAYAKAN BISNIS DAN PERAN KESATUAN PENGELOLA HUTAN LAKITAN DI KABUPATEN MUSI RAWAS PROVINSI SUMATERA SELATAN - Dian Amalina; Dessy Andriani; Elisa Wildayana (Publikasi Penelitian Terapan dan Kebijakan, 2022)
The objectives of this study were (1) to analyze the role and interests of the KPH Lakitan Musi Rawas Regency in the development of honey business, (2) to analyze the financial feasibility of forest honey management in KPH Lakitan Musi Rawas Regency and to ( 3) to analyze strategies for developing forest honey in KPH Lakitan Musi Rawas District based on financial feasibility and the results of mapping the roles and interests of KPH Lakitan. The sample in this study consisted of 20 of which 3 of them were expert samples from internal KPH Lakitan and 17 of them were forest honey hunters. This paper concludes that based on mapping the roles and interests of KPH Lakitan are dominant in quadrant B, which means that the contribution of facilities and involvement of stakeholders as well as contribution of human resources and linkages between programs from the planning stage to the monitoring stage has been implemented properly. Meanwhile, the result of financial feasibility analysis of the forest honey management business is feasible to continue because, the NPV results were positive > 0, that means the investment will get net benefits. After that, from the result of the SWOT analysis of KPH Lakitan forest honey management, the strategy that can be formed is SO strategy formulation namely by utilizing government support in expanding the marketing network and developing honey bee cultivation technology.